Toddlers expect ingroup loyalty to override personal preferences when outgroups are present - Lin Bian; Renée Baillargeon (Proceedings of the National Academy of Sciences, 2026)
When outgroups are present, adults may endorse ingroup choices that are at odds with their personal preferences, in an outward show of ingroup loyalty. Here, we examined whether 2-y-old toddlers ( N = 108) might already understand such shows of loyalty. In three violation-of-expectation experiments, toddlers watched interactions among a target individual, an ingroup member, and an outgroup member; group memberships were marked with novel labels. In the critical trials, the target individual chose between an ingroup- and an outgroup-associated toy. When the outgroup member was present during this selection process, toddlers expected the target individual to conform to her group’s norm and select the ingroup-associated toy, even when they knew she preferred the outgroup-associated toy. This was true whether or not the ingroup member remained in the scene; as long as the outgroup member was present, toddlers expected the target individual to select the ingroup-associated toy and no other toy. When the outgroup member was absent, however, toddlers expected the target individual to act on her personal preference, if any. They also held this expectation if no information was provided about group memberships. Together, these results indicate that by 2 y of age, toddlers a) construe individuals as possessed of both a personal and a social identity, b) understand that individuals may produce different actions in different contexts depending on which identity has precedence, and c) expect individuals’ social identity to take precedence in intergroup contexts even when it conflicts with their personal identity, in a show of ingroup loyalty.